A CRITIQUE ON LEASE VERSUS BUY ANALYSIS AND GOVERNMENT TAX REVENUE - Wang, Guan Jun (International Journal of Accounting & Finance Review, 2021)
Motivation for leasing is often believed to be the tax rate difference between the lessee and the lessor, allowing both to save on taxes at the government’s expense. These short notes challenge this conventional wisdom and demonstrate not only the tax rate difference but also other various leasing parameters that can have an impact on government tax revenue both analytically and numerically. This paper adds additional theoretical groundworks to the literature to support the claim that the positive-sum games do exist among the lessee, the lessor, and the government. JEL Classification Codes: C6, G3.